Bioactive glass scaffold architectures regulate patterning of bone regeneration in vivo. (September 2020) - Shi, Xiaomeng; Nommeots-Nomm, Amy; Todd, Naomi M.; Devlin-Mullin, Aine; Geng, Hua; Lee, Peter D.; Mitchell, Christopher A.; Jones, Julian R.
Highlights: This is the first article that compares architectures of bioactive glasses in vivo : Additive Manufactured Bioactive glass v traditional cancellous bone-like foam architecture. We matched the modal interconnect size of the foam scaffolds, i.e. the windows between pores, to the channel sizes of the 3D printed scaffolds. The cancellous bone-like foam scaffold initially encouraged more rapid bone ingrowth than the printed scaffold, due to its rapid degradation, with final bone morphology similar to that of the empty defect, while the higher strength printed scaffold showed longer term sustained regeneration. Bone growth was observed first in concave pores of the foam and in the concave corners of the 3D printed pore channels. Correlative imaging quantified the bone ingrowth throughout the defects/scaffolds in 3D, using a volume of interest. Abstract: The architecture of bone scaffolds, such as pore dimensions, connectivity and orientation can regulate osteogenic defect repair, as can their rate of degradation. Synthetic bone grafts have historically been developed with foam structures to mimic trabecular bone. Now, Additive Manufacturing techniques enable production of open and regular pore architectures with improved compressive strengths. Here, we compare two types of bioactive glass scaffolds, made of the highly biodegradable ICIE16 composition, with distinctively different architectures but matched interconnect sizes ( 150 µm), produced via two different techniques: gel-cast foaming and direct ink writing. A rabbit lateral femoral defect model was used to compare the effect of their architecture on in vivo bone regeneration, relative to a defect only control group, after 4 and 10 weeks of implantation. 3D X-ray microcomputed tomography (micro-CT), correlated to histology and back-scatter electron microscopy (BS-SEM) permitted quantitative evaluation of new bone ingrowth and degradation of the scaffolds. Both foam and printed scaffolds showed equal or higher bone ingrowth compared to the control group. After 4 weeks, the foam group showed the highest osteogenesis, with 51% more bone ingrowth than the defect only controls, but after 10 weeks the defect treated with the printed scaffold had the most bone ingrowth (40% more than the empty defect). Energy dispersive X-ray (EDS) mapping revealed degradation of the glass and calcium-phosphate deposition. The foam group showed more rapid degradation than the printed group, due to higher total porosity (even though interconnected pore size was equivalent). The foam scaffold appeared to allow rapid bone ingrowth and cancellous bone formation, whereas the printed scaffold seemed to provoke cortical-like bone formation, while remaining in place for longer than the 10 week study. While the foam's concave architectures promote initial bone ingrowth, the higher strength open pore channels of the printed scaffolds are beneficial for scaffolds made of highly degradable bioactive glasses. Graphical abstract: Image, graphical abstract